(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2023)
The principles of alternative justice dispute resolution mechanisms configure a scaffolding for dialogue, consensus and flexibility of access to justice beyond the justice administration system. It stipulates a plural and democratic way of inclusion and non-discrimination in various contexts of daily life, using and potentiating the principles of dispute resolution mechanisms in professional, work and personal fields, underlies a peaceful way in the management of conflict with empathy and active listening. For this reason, this document intends to describe the importance of alternative justice through dispute resolution mechanisms through the principles that constitute it, since it is considered that it is the area in which it is applied or developed, alternative justice has its substantive basis. in these principles that are considered essential to keep in mind.